THE USE OF JAZZ CHANTS TO DEVELOP YEAR 3 PUPILS’ ABILITYTO CONSTRUCT SIMPLE SENTENCES - Dina Syafiqa Annur Azhar; Sri Ranjani Naidu (Proceedings of The ICECRS, 2016)
This action research attempts to improve teacher’s classroom teaching in developing pupils’ ability to construct simple sentences. Jazz chanting was adapted to teach writing skills and was used as the intervention. This research aimed to describe the extent the use of jazz chants was able to develop Year 3 pupils’ ability to construct simple sentences effectively. Three research participants were chosen among year 3 pupils. The participants were purposefully identified as they had encountered difficulties in constructing simple sentences. Three lessons to exploit the intervention were conducted in this research. The data collection methods that were used in this research to gain insights into the effectiveness of the teacher’s teaching strategy were document analysis consisting of worksheets and a pre-test and a post-test, observation and a semi-structured interview with the participants. The research findings revealed that the teaching with the use of the intervention, jazz chanting, was able to positively impact two participants in constructing simple sentences effectively.Meanwhile, triangulation of the various data also indicated that the teaching aided by the intervention failed to have the expected impact on one participant. Discussion of the research findings and conclusion had highlighted the researcher’s pertinent reflection and suggestions for further improvement on the intervention and for future research.